Implementation of Children's Music-Based Rhythmic Gymnastics Learning Model to Improve Motor Coordination of Grade V Students of SDN Kertagena Tengah 4 - Paedi, Paedi; Hadi, Antonius Prasetyo (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2024)
Classroom Action Research aims to enhance the motor coordination of grade V students at SDN Kertagena Tengah 4 through the implementation of a music-based rhythmic gymnastics learning model for children. The background of the study is based on the low motor coordination ability of students (only 32% reached the initial competency standards) and the lack of variation in PJOK learning methods. This study employed the Kemmis and McTaggart model of the PTK approach, utilising two intervention cycles. Data were collected using the Gross Motor Development Checklist instrument (α = 0.85), the Rhythmic Movement Observation Rubric (content validity = 0.82), observations, interviews, and students' diaries. The results showed significant improvements in rhythmic accuracy (from 35% to 92%), postural control (from 28% to 88%), and active participation (from 44% to 90%). Additionally, qualitative data revealed an increase in learning motivation, self-confidence, and the use of natural peer tutoring. This research demonstrates the effectiveness of a multisensory approach (combining auditory, visual, and kinesthetic elements) in learning gymnastics. The results of this study have practical benefits for both teachers and schools in developing an innovative and student-centered PJOK curriculum.